Learning Methods in the Era of Society 5.0: Implications of the Islamic Education System within the Merdeka Curriculum - Dinanti, Neswa Putri; Asri, Fatma Mulyana; Azzahra, Azil Hanifa; Sabri, Ahmad; Hidayatullah, Rully (Journal of Regional Development and Technology Initiatives, 2024)
This paper delves into the dynamic realm of learning methods within the context of the Era of Society 5.0, an era characterized by rapid technological advancement and profound societal transformations. As traditional educational paradigms are being reshaped, there is a growing recognition of the need for innovative approaches that equip learners with the skills and mindset necessary to thrive in an ever-evolving landscape. Central to this discussion is the exploration of the Merdeka Curriculum, a pedagogical framework that emphasizes autonomy, critical thinking, and adaptability. By empowering learners to take ownership of their education and cultivate a deeper understanding of the world around them, the Merdeka Curriculum seeks to prepare individuals for the complexities of the modern world. Within this framework, the integration of the Islamic education system presents unique opportunities to enrich the educational experience. Islamic principles, which emphasize ethics, morality, and spirituality, can serve as a guiding light in navigating the complexities of contemporary society. By incorporating these principles into the curriculum, educators can foster a sense of identity, purpose, and belonging among learners while also promoting values-based education that transcends cultural boundaries. Moreover, by embracing diversity and inclusivity, the Merdeka Curriculum can serve as a platform for promoting intercultural dialogue and understanding, fostering a sense of global citizenship among learners. Through this exploration, we aim to shed light on the transformative potential of integrating the Islamic education system into the Merdeka Curriculum, highlighting the synergies that emerge when tradition meets innovation in the pursuit of holistic education.